Increased elongase and desaturase gene expression with stearidonic acid enriched diet does not enhance long-chain (n-3) content of seawater Atlantic salmon ( Salmo salar L.) - Miller, MR; Bridle, AR; Nichols, PD; Carter, CG (The Journal of Nutrition, 2008)
Atlantic salmon (Salmo salar L.) can produce (n-3) long-chain (LC)-PUFA when fed biosynthetic precursors. This haspotential for developing sustainable aquafeeds. Echium oil (EO) is rich in stearidonic acid [SDA; 18:4(n-3)] and bypasses theinitial D6 desaturase (FAD6) step in the (n-3) LC-PUFA biosynthetic pathway. EO was fed to seawater Atlantic salmon for12 wk and compared with fish fed a diet containing canola oil (CO), a source of a-linolenic acid [ALA; 18:3(n-3)] or fish oil(FO) that provides (n-3) LC-PUFA. Fatty acid (FA) composition of liver, white muscle, and whole fish was measured toshow whether dietary precursors were endogenously biosynthesized to LC-PUFA. Gene expression of liver FA elongaseand FAD5 was upregulated in EO fish compared with FO fish. Furthermore, dietary precursors affected the FAconcentrations of direct biosynthetic products in all tissues. The increased gene expression in the EO fish was reflected byan increased FA concentration of eicosapentaenoic acid [20:5(n-3)] in the liver compared with the CO fish. However, thehigh concentrations of (n-3) LC-PUFA found in seawater Atlantic salmon fed diets rich in FO were not attained viabiosynthesis from precursors (ALA or SDA) in diets.